The effectiveness of non-surgical intervention (Foot Orthoses) for paediatric flexible pes planus: A systematic review: Update. - Sindhrani Dars; Hayley Uden; Helen A Banwell; Saravana Kumar (PLoS ONE)
Background Flexible pes planus (flat feet) in children is a common presenting condition in clinical practice due to concerns amongst parents and caregivers. While Foot Orthoses (FOs) are a popular intervention, their effectiveness remains unclear. Thus, the aim of this systematic review was to update the current evidence base for the effectiveness of FOs for paediatric flexible pes planus. Methods A systematic search of electronic databases (Cochrane, Medline, AMED, EMBASE, CINHAL, SportDiscus, Scopus and PEDro) was conducted from January 2011 to July 2017. Studies of children (0-18 years) diagnosed with flexible pes planus and intervention to be any type of Foot Orthoses (FOs) were included. This review was conducted and reported in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. McMaster critical review form for quantitative studies, was used to assess the methodological quality of the included studies. Given the heterogeneity of the included studies, a descriptive synthesis of the included studies was undertaken. Results Out of 606 articles identified, 11 studies (three RCTs; two case-controls; five case-series and one single case study) met the inclusion criteria. A diverse range of pre-fabricated and customised FOs were utilised and effectiveness measured through a plethora of outcomes. Summarised findings from the heterogeneous evidence base indicated that FOs may have a positive impact across a range of outcomes including pain, foot posture, gait, function and structural and kinetic measures. Despite these consistent positive outcomes reported in several studies, the current evidence base lacks clarity and uniformity in terms of diagnostic criteria, interventions delivered and outcomes measured for paediatric flexible pes planus. Conclusion There continues to remain uncertainty on the effectiveness of FOs for paediatric flexible pes planus. Despite a number of methodological limitations, FOs show potential as a treatment method for children with flexible pes planus. Prospero registration number CRD42017057310.